RECENSIÓN DE: GONZÁLEZ SÁNCHEZ, I. (2021). NEOLIBERALISMO Y CASTIGO, BARCELONA, BELLATERRA EDICIONS, 2021 - Fernández Abad, Carlos (Revista de Derecho Penal y Criminología, 2022)
RECENSIÓN DE: GONZÁLEZ SÁNCHEZ, I. (2021). NEOLIBERALISMO Y CASTIGO, BARCELONA, BELLATERRA EDICIONS, 2021